ANALYSIS OF VALIDITY, RELIABILITY AND FEASIBILITY OF STUDENT CONFIDENCE ASSESSMENT INSTRUMENTS - Maulana, Andi (Schola, 2023)
This research is part of a research on the development of student self-confidence assessment for elementary school. The purpose of this study was to determine the content validity and reliability of an instrument. The instrument developed was in the form of a questionnaire sheet. Content analysis and observation sheets used Coefficient V by Aiken's while Reliability used Cronbach's Alpha with the help of Ms. Excel. The results of this study indicate that: the questionnaire sheet in the form of a scoring rubric and this research proved valid, the highest with a coefficient of V Aiken s 0.74 and reliable with a coefficient of Cronbach's Alpha = 0.76 which means high. The instrument's feasibility test also shows 100% of the statement items are eligible to be used. Based on the results of this study, the assessment of increasing student self-confidence is appropriate to use.